Variación de ingresos en el área de tesorería del Gobierno Autónomo Descentralizado Parroquial Ricaurte en los periodos 2021 y 2022. - Cotera Pita, Bryan Danilo (2023)
The present case study was carried out in the Ricaurte Parish GAD with the objective of determining the variation in income in the periods 2021 and 2022. The work was constituted through a mixed approach, documentary and field research, as well as an inductive method. In addition, the interview technique was used, which was directed to the Financial Director of the GAD and a documentary analysis of the income with its respective instruments. The results were: the institution has the following sources of income: current income, capital and financing; The GAD has a marked dependence on budget allocations from the State; The institution does not have appropriate management capacity regarding the generation of income for the development of various projects by the GAD; and in 2021 the entity presented deviations in one of its sources of income, since the management of accounts receivable was not completely effective. The GAD presented a reduction in financing income in the periods analyzed. However, the period where the negative variation was important is 2021, where a percentage deviation of 54% of what was expected to enter in this area was identified. As conclusions.